2006
DOI: 10.1093/carcin/bgl152
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 protects against UVB induced apoptosis by preventing release of cathepsins and cytochrome c in human melanocytes

Abstract: Stress-induced heat shock protein 70 (Hsp70) effectively protects cells against apoptosis, although the anti-apoptotic mechanism is still undefined. Exposure of human melanocytes to heat and subsequent UVB irradiation increased the level of Hsp70 and pre-heating reduced UVB induced apoptosis. Immunofluorescence staining of Hsp70 in combination with staining of lysosomes (Lamp2) or mitochondria (Mitotracker Ò ) in pre-heated UVB exposed cells showed co-localization of Hsp70 with both lysosomes and mitochondria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
77
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 38 publications
2
77
0
3
Order By: Relevance
“…The addition of lysosomal protease inhibitors or anti-cathepsin-D reduced caspase-8 activation and nuclear fragmentation, indicating that both cysteine and aspartic cathepsins work upstream of caspase-8 activation in UVA-irradiated keratinocytes. In melanocytes, UVA-induced apoptosis is mediated by lysosomal membrane permeabilization and release of cathepsins to the cytosol (Bivik et al, 2007). It has been suggested that cathepsin D activates caspase-8 in in vitro experiments (Conus et al, 2008;Conus et al, 2012), which further supports our findings.…”
Section: Discussionsupporting
confidence: 90%
“…The addition of lysosomal protease inhibitors or anti-cathepsin-D reduced caspase-8 activation and nuclear fragmentation, indicating that both cysteine and aspartic cathepsins work upstream of caspase-8 activation in UVA-irradiated keratinocytes. In melanocytes, UVA-induced apoptosis is mediated by lysosomal membrane permeabilization and release of cathepsins to the cytosol (Bivik et al, 2007). It has been suggested that cathepsin D activates caspase-8 in in vitro experiments (Conus et al, 2008;Conus et al, 2012), which further supports our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Although it is clear that HSP70 has a general anti-apoptotic function, the mechanism is not known. Some studies have shown that HSP70 affects processes that regulate apoptotic signaling, effecter molecule activation, events downstream of caspase activation, release of cathepsins, cytochrome c, apoptosis-inducing factor (AIF), and even the death-associated permeablization of lysosomes (Feng et al 2006;Lui and Kong 2007;Bivik et al 2007;Matsumori et al 2005;Nylandsted et al 2004). Mitochondria harbor three key modulators of apoptosis: cytochrome c, AIF, and Smac (Kroemer and Reed 2000 Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Cell surface localization of chaperones has been reported in several studies [49][50][51]. HSP70, previously characterized as a chaperone, regulates apoptosis in response to heat shock and oxidative stress by preventing the release of cathepsins and cytochrome c [52]. This protein prevents lysosome-mediated sudden death by binding to lysosomal cathepsins B, D, L and H and providing structural stability to lysosomal membranes [37,53].…”
Section: Protein Identificationmentioning
confidence: 97%